Chemistry of bimetallic, chalcogenide and highly reactive metal nanoparticles - Bhatia, Geetanjali; advised by Jagirdar, Balaji R (Bangalore: Indian Institute of Science, 2023)
The remarkable modifications in the characteristics of materials on a nanoscale, caused by surface effects, quantum confinement, and dependence on shape, leads to diverse applications of nanomaterials, such as in catalysis, environmental applications, energy conversion and storage, etc. Research on nanomaterials is extensively concentrated on metal nanoparticles, particularly those made of noble metals and various transition metal elements, as well as systems that utilize these metals. However, research on systems based on post-transition elements, such as Sn, has remained relatively underdeveloped. This is because these elements have a strong affinity for oxygen and a low affinity towards most surfactants, making controlled synthesis of their size and shape challenging. Besides that, researchers have also been drawn to various other types of nanomaterials, including alloys, intermetallics, chalcogenides, and more. In addition, the synthesis of nanomaterials with a particular emphasis on their usage in energy storage applications is a significant area of research. Achieving a controlled and scalable synthesis of nanomaterials is the primary challenge in the field of nanoscience. Out of the many techniques available, solution-based chemical synthesis strategies provide an effective and straightforward approach to producing nanomaterials. The solution-based synthesis offers control over size and shape of nanomaterials by providing a convenient medium for their growth and carries the advantage of greater flexibility compared to the dry synthetic routes. In this direction, the digestive ripening technique in combination with solvated metal atom dispersion method (SMAD) is one of the exceptional solution-based synthesis methods for creating nanomaterials. This thesis is dedicated to demonstrating a solution-based synthesis of a broad range of nanomaterials, including alloys, intermetallics, and chalcogenides, and to investigate their potential for various applications. The research also delves into the synthesis and characterization of highly reactive nanomaterials, such as magnesium-carbon composites, which are essential for hydrogen energy storage.
includes bibliographical references and index
PhD; 2023; Inorganic and Physical Chemistry
Keywords: Digestive ripening; bimetallic nanoparticles